If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -6 = 8x + 11 Reorder the terms: -6 + 9x = 8x + 11 Reorder the terms: -6 + 9x = 11 + 8x Solving -6 + 9x = 11 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -6 + 9x + -8x = 11 + 8x + -8x Combine like terms: 9x + -8x = 1x -6 + 1x = 11 + 8x + -8x Combine like terms: 8x + -8x = 0 -6 + 1x = 11 + 0 -6 + 1x = 11 Add '6' to each side of the equation. -6 + 6 + 1x = 11 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = 11 + 6 1x = 11 + 6 Combine like terms: 11 + 6 = 17 1x = 17 Divide each side by '1'. x = 17 Simplifying x = 17
| 5p-0.48=0.12 | | 2y-1=5y-10 | | 3/4x4/9 | | h=6+17t-16t+2 | | 7w*2w^8v^4*3v^2= | | 0=91+13t | | x/-6+7=0 | | 3+d/2=10 | | (x-3)/(x^3-9x^2+24x-18) | | 12-11s=45 | | b*b^2= | | 15=-11c+4 | | x+3y+2-3x-5y=4 | | y^3*y^2= | | 4-k/5=18 | | 0.006x-11440/x^2=0 | | 13/4-x/2 | | 6y=4-2x | | 11/6x-4 | | -19=4+3x | | 7/4+9/4 | | 15=6+m/6 | | -2/3u-8/7=-1/2 | | c+l/c-2=4/7 | | 4x-2=28.4 | | 12d-6=138 | | 2+m/3=0 | | 4+4x/5+3-x/2=41/10 | | 17a^2+9b^2=X | | 5+k/9=-31 | | 5(x-7)=3/2x+15 | | 9/w=-6 |